Isolated unilateral left upper lobe agenesis causing recurrent pneumonia: A case report - Agrawal, Jyoti; Gupta, Mukesh (Journal of Nepal Paediatric Society, 2016)
Lung agensis is a rare developmental anomaly. It can range from total bronchial and parechymal agensis to mild pulmonary parenchymal hypoplasia of one or both lungs. A case of lobar agenesis of the left upper lung in a three month old girl causing recurrent chest infection is presented. J Nepal Paediatr Soc 2015;35(2):175-176